1994
DOI: 10.1007/bf02353193
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of childhood depression: Using comorbidity and symptom overlap to generate multiple hypotheses

Abstract: Childhood depression is often found to share symptoms and coexist with several other childhood disorders and physiological conditions, leading to diagnostic errors and possibly inappropriate treatment. Literature relevant to the differential diagnosis of childhood depression is reviewed with particular attention given to the similarities and differences between depression and coexisting conditions such as anxiety disorders, conduct disorders, and attention deficit hyperactivity disorder. The characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
0
7
0
2
Order By: Relevance
“…At the syndromal level, rates of comorbidity between internalizing and externalizing disorders appear quite high (Angold et al 1999, de Mesquita and Gilliam 1994, Woolston et al 1989. Comorbidity between conduct disorder and comorbid internalizing disorders are common in adults, with odds ratios (ORs) ranging from 1.6 (MDD, p<0.05) to 4.2 (post-traumatic stress disorder, p<0.05; Nock et al 2006), with only agoraphobia (OR=1.4) not reaching statistical significance in the study.…”
mentioning
confidence: 80%
“…At the syndromal level, rates of comorbidity between internalizing and externalizing disorders appear quite high (Angold et al 1999, de Mesquita and Gilliam 1994, Woolston et al 1989. Comorbidity between conduct disorder and comorbid internalizing disorders are common in adults, with odds ratios (ORs) ranging from 1.6 (MDD, p<0.05) to 4.2 (post-traumatic stress disorder, p<0.05; Nock et al 2006), with only agoraphobia (OR=1.4) not reaching statistical significance in the study.…”
mentioning
confidence: 80%
“…For example, DSM-5 diagnostic criteria of major depression disorder state that children might not show sad, but irritable mood [45]. Depressed children might report unspecific somatic complaints [46] or depression might result in attention problems, leading to misdiagnosis of depressed children as having learning disorders [47]. Similarly, adolescents with substance abuse might show symptoms of learning disabilities [48].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies in Western populations have also found significant comorbidity of mental health problems (de Mesquita & Gilliam, 1994; Kessler, et al, 2009; Kessler, Merikangas, & Wang, 2007). For Western clinicians, symptom overlap between disorders and widespread “true” comorbidity among syndromes contributes to “clouding” of diagnostic differentiation (de Mesquita & Gilliam, 1994). Further research is needed to determine how much of this overlap is due to sharing of symptoms among two or more syndromes as opposed to comorbidity.…”
Section: Discussionmentioning
confidence: 99%